Aspectos epidemiológicos dos pólipos e lesões plano-elevadas colorretais - Torres Neto, Juvenal da Rocha (2010)
Introduction: Colorectal polyps and flat injuries are important for the prevention of colorectal cancer due to the malignancy of adenomas. Objective: To describe the demographic profile of patients with endoscopic diagnosis of colorectal polyps and/or flat injuries at University Hospital of Universidade Federal de Sergipe and Torres Medical Center. Methods: A total of 6,919 records were evaluated from January 2002 to December 2007 with respect to the following variables: age, gender, origin, indication; injury evaluation os number, size, morphology, histology, dysplasia degree, topography; synchronics and metachronics injuries and associated diagnoses. Results: 1,031(13.51%) colorectal polyps and flat injuries were found in 935 tests, accounting for 826 patients, 46% males and 54% females. The age ranged from 3 to 96 years with average of 53.64. The most frequent topographic distribution of polypoid injuries were rectum and sigmoid (58.40%). The injuries were sessile in 52.80% of the cases, pedicle in 27.90%, and flat injuries in 19.30%. There were synchronical injuries in 23.48% of patients and metachronic in 22 patients. Histologically, 43.36% were adenomas, being 85.70% tubular, 9.60% tubulovillous and 4.70% villous; hyperplastic polyps were found in 30.64% of the cases, inflammatory in 15.80% and 10.20% presented other histological types. The adenomas showed low-grade dysplasia in 83.40% and high degree in 16.60% of the patients. Seven were adenoma-carcinomas, one was carcinoid and one was gastrointestinal stromal tumor. Conclusions: The colonoscopy and polypectomy are important in diagnosis and prevention of colorectal cancer.